2000
DOI: 10.1177/004051750007001201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Changes in Knit Structure and Density on the Mechanical and Hand Properties of Weft-Knitted Fabrics for Outerwear

Abstract: This study focuses on the mechanical properties of weft knits for outerwear as a function of knit structure and density and the relationships between hand, structure, and density. Eighteen weft knits are produced with six different structures (1 × 1 rib, half-cardigan rib, half-milano rib, interlock, single-pique, and crossmiss interlock) and three different densities (loose, medium, tight). The mechanical properties and hand values of the fabrics are measured using the KES-F method. Tensile properties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 20 publications
0
61
0
2
Order By: Relevance
“…2006a) and twist (Chattopadhyay and Banerjee 1996; Sahnoun 2002). Furthermore, it has been also observed that weave and knit structure (Choi and Ashdown 2000; Behery 2005; Ben Said et al . 2006b) and fabric density (Choi and Ashdown 2000; Sahnoun 2002) affected the tactile feeling of fabrics.…”
Section: Introductionmentioning
confidence: 91%
“…2006a) and twist (Chattopadhyay and Banerjee 1996; Sahnoun 2002). Furthermore, it has been also observed that weave and knit structure (Choi and Ashdown 2000; Behery 2005; Ben Said et al . 2006b) and fabric density (Choi and Ashdown 2000; Sahnoun 2002) affected the tactile feeling of fabrics.…”
Section: Introductionmentioning
confidence: 91%
“…In their work, the properties were estimated as a structural body and not as a continuum in terms of the displacement of individual yarns and fibers in the fabric by external applied load. In spite of a number of established works [6][7][8][9][10][11][12][13][14][15] concerning excellent fabric-deformation theory based on fabric structure mechanics, any theoretical methods of fabrics were out of the framework of their structural changes under extension and recovery processes. Certainly, the analysis of hysteresis under extension and recovery routes is a difficult problem and there is no fundamental concept in any material science fields.…”
Section: And Tomoko Yamadamentioning
confidence: 99%
“…Several researchers have studied the effect of process parameters on the fabrics' tactile quality. They have reported that sensory feeling is affected by structure parameters such as material, yarn properties and weaving or knitting conditions (Chattopadhyay and Banerjee 1996; Choi and Ashdown 2000; Sahnoun 2002; Behery 2005; Ben SaĂŻd 2007). In contrast, few studies have examined the influence of finishing treatments on tactile properties of fabrics.…”
Section: Introductionmentioning
confidence: 99%